Partial characterization of nine bacteriocins produced by lactic acid bacteria isolated from cold-smoked salmon with activity against listeria monocytogenes - Tomé, Elisabetta (2010)
Nine LAB bacteriocin-producers, isolated from vacuum-packaged cold-smoked salmon (CSS), were phenotypically and genotypically identified as Lactobacillus curvatus, Lactobacillus delbrueckii, Lactobacillus fermentum, Enterococcus faecium, and Pediococcus acidilactici. Their bacteriocins were partially characterized. The antimicrobial spectrum was determined against Listeria monocytogenes, E. faecalis, E. faecium, and Staphylococcus aureus. The molecular size of bacteriocins ranged from 2.8 to 4.5 kDa. They were inactivated by treatment with proteolytic enzymes but not by lipolytic or glycolytic enzymes. Maximal activity against L. monocytogenes ranged between 800 and 10000 AU/mL at pH 6.5. Most of the bacteriocins maintained full activity in a pH range of 2.0 to 8.0 but were partially or completely inactivated at pH 10.0. After heating at 60°C and 100°C, only two bacteriocins from Lb. curvatus strains partially lost activity. All bacteriocins showed a narrow spectrum of activity and a high anti-listerial activity, which is characteristic of the class IIa bacteriocins. Isolated bacteriocinproducing LAB could be used successfully in the bio-preservation of CSS and development of new potential bio-preservatives for CSS active against L. monocytogenes.